Australians at Risk: Management of Cardiovascular Risk Factors in the REACH Registry - Reid, Christopher; Nelson, M.; Shiel, L.; Chew, D.; Connor, G.; DeLooze, F. (Elsevier, 2008)
Background and Rational: Atherothrombosis is the leading cause of cardiovascular morbidity and mortality in Australia and around the world. The evidence base for appropriate management of these subjects has increased over the past decade through the conduct of randomised controlled trials. However little is known of the translation of evidence into clinical practice in terms of current management practice and risk factor control in high-risk patients in Australia. Methods: As part of the international REACH (Reduction of Atherothrombosis for Continued Health, protocol number C_8903) Registry, subjects at high risk of atherothrombosis based on the presence of multiple risk factors or overt coronary artery (CAD), cerebrovascular (CVD) or peripheral arterial disease (PAD) underwent a cardiovascular risk factor review. Demographic data and current medication management was also assessed. The subjects were recruited entirely through Australian general practice. Results: Globally 67,888 patients were involved in the REACH registry of whom 2783 were recruited from 273 general practitioners around Australia. In comparison to the global population sample the Australian cohort was older (72 years versus 68 years) and had a lower prevalence of current smoking (7% versus 14%). Seventy-three percent of the Australian cohort had CAD and 15% had vascular disease in more than one location. Seventy-four percent of the cohort was either overweight or obese. Despite the widespread use of antihypertensive and lipid lowering therapy, half of the total group had a blood pressure recorded as =140/90 mmHg and 24% of the cohort had a total cholesterol level >5.2 mmol/L. Conclusion: The REACH registry offers the opportunity to provide a better understanding of the management of cardiovascular risk factors in patients at high-risk of atherothrombosis in Australia. Reducing the high rates of overweight and obesity and increasing the proportion of patients achieving therapeutic targets should remain priority areas in the management of this group of high-risk patients. © 2007 Australasian Society of Cardiac and Thoracic Surgeons and the Cardiac Society of Australia and New Zealand.